(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2016)
In 1789 the printer Remondini published four editions of Savioli’s Amori. This fact reveals the remarkable success achieved by the work, which was edited for the first time in 1765. By analysing the volumes of each printing, it is argued that the identical frontispieces of the four Remondini printings actually hide four original editions resulted from a complete recomposition of the matrices. It is likely that such a high number of editions depended on a renewed interest in Savioli’s work, stimulated by the publication of some letters printed by Nicolò Orcesi in the same year.